СORRECTION OF AUTOIMMUNE GLOMERULONEPHRITIS BY LETHAL IRRADIATION AND TRANSFER OF SYNGENEIC BONE MARROW CELLS IN AN EXPERIMENTAL MODEL - O. T. Kudaeva; E. V. Goiman; E. V. Nenasheva; I. V. Majborodin; O. P. Kolesnikova; V. A. Kozlov (Медицинская иммунология, 2014)
Mice with lupus-like autoimmune glomerulonephritis induced by chronic graft-versus-host reaction, have been treated with irradiation at lethal doses, followed by injection of bone marrow cells from syngeneic donors. Following such treatment, the autoimmune process was interrupted, as judged by disappearance of anti-DNA autoantibodies in peripheral blood. A drop in urine protein to normal values was also observed in the marrow recipients, thus being a characteristic sign of recovery from glomerulonephritis. Correction of the disease was confirmed by morphological data: the signs of oedema were diminished, and inflammatory reaction was found to be decreased in the kidneys of animals with lupus-like disorder after marrow transplantation.